[2.2]Paracyclophane-Based Chiral Platforms for Circularly Polarized Luminescence Fluorophores and Their Chiroptical Properties: Past and Future - Sugiura, Ken-ichi (Frontiers in Chemistry, 2020)
Quality of CPL fluorophore is defined by the vectors of electric dipole transition moment and imaginary magnetic dipole transition moment. The aim of this review is to introduce readers to a chiral moiety applicable to CPL studies focusing on chiral cyclophanes because the rigid cyclophanes are able to hold the vector directions of electric dipole transition moment and imaginary magnetic dipole transition moment.